Solving The Price Is Right : How Mathematics Can Improve Your Decisions on and off the Set of America's Celebrated Game Show /: How Mathematics Can Improve Your Decisions on and off the Set of America's Celebrated Game Show. (2023) - Bergner, Justin L
No abstract available